Manajemen Mutu Kurikulum Dalam Meningkatkan Kualitas Pendidikan SMA Darut Taqwa Purwosari - Riski Setiawan; Achmat Mubarok (AL-Ikhtiar : Jurnal Studi Islam, 2025)
The curriculum plays an important role in the learning process in an educational institution. A well-designed curriculum will produce students who are competent and think realistically towards the future in accordance with national education goals. Describe the implementation of curriculum management at SMA Darut Taqwa Purwosari in supporting the learning process. To identify and analyze the obstacles faced in the implementation of curriculum management and find effective solutions at SMA Darut Taqwa. The type of research used in this study is a case study. Case Study is a series of scientific activities carried out intensively, in detail and in depth about a program, event, and activity, both at the individual level, a group of people, an institution, or an organization to gain in-depth knowledge of the event. The results of these findings are Efforts to improve the quality of the curriculum through 1). Planning. In planning there are findings through the national curriculum and local curriculum, S1 and certified teachers, learning structure, learning curriculum structure, Workshop, IHT, Supervision and National Assessment. 2). Organizing. In organizing there are findings through. Curriculum grouping, Curriculum, Curriculum developers and Learning Committee. 3). Implementation. In the implementation, there are findings through cognitive, affective and psychomotor competencies, preparation of learning frameworks, CP, TP and ATP. 4). Evaluation. In the evaluation, there are findings through evaluations every semester, Complex, Cluster and Supervision. And there are also supporting and inhibiting factors. For supporting factors, there are two, namely internal and external, while for inhibiting factors there is only one, namely technology. kurikulum memegang peranan penting terhadap proses pembelajaran dalam suatu lembaga pendidikan. Sebuah kurikulum yang dirancang dengan baik maka akan menghasilkan peserta didik yang berkompetensi dan berfikir realistis menuju masa depan sesuai dengan tujuan pendidikan nasional. Mendeskripsikan pelaksanaan manajemen kurikulum di SMA Darut Taqwa Purwosari dalam mendukung proses pembelajaran.Untuk mengidentifikasi dan menganalisis kendala yang dihadapi dalam pelaksanaan manajemen kurikulum serta menemukan solusi yang efektif Di SMA Darut Taqwa. Jenis penelitian yang digunakan pada penelitian ini adalah studi kasus. Studi Kasus ialah suatu serangkaian kegiatan ilmiah yang dilakukan secara intensif, terinci dan mendalam tentang suatu program, peristiwa, dan aktivitas, baik pada tingkat perorangan, sekelompok orang, lembaga, atau organisasi untuk memperoleh pengetahuan mendalam tentang peristiwa tersebut. Hasil dari temuan ini adalah Upaya peningkatan mutu kurikulum melalui 1). Perencanaan. Dalam perencanaan terdapat temuan melalui kurikulum nasional dan kurikulum lokal, Guru S1 dan sudah sertifikasi, Struktur pembelajaran, Struktur kurikulum pembelajaran, Workshop, IHT, Supervisi dan Asesmen Nasional.2). pengorganisasian. Dalam pengorganisasian terdapat temuan melalui. Pengelompokan kurikulum, Kurikulum, Pengembang kurikulum dan Komite pembelajaran. 3). Pelaksanaan. Dalam pelaksanaan terdapat temuan melalui kompetensi kognitif, Afektif dan Psikomotorik, Penyusunan kerangka pembelajaran, CP, TP dan ATP. 4). Evaluasi. Dalam evaluasi terdapat temuan melalui Evaluasi setiap semester, Kombel, Rumpun dan Supervisi. Dan juga ada faktor pendukung dan penghambat, Untuk faktor pendukung itu ada dua yaitu internal dan eksternal sedangkan untuk faktor penghambat Cuma ada satu yaitu pada teknologi